Restoration of Degraded Alpine Meadows Improves Pollination Network Robustness and Function in the Tibetan Plateau - Gao, Erliang; Wang, Yuxian; Bi, Cheng; Kaiser-Bunbury, Christopher N.; Zhao, Zhigang (Frontiers in Ecology and Evolution, 2021)
Ecological restoration is widely used to mitigate the negative impacts of anthropogenic activities. There is an increasing demand to identifying suitable restoration management strategies for specific habitat and disturbance types to restore interactions between organisms of degraded habitats, such as pollination. In the Tibetan Plateau, alpine meadows have suffered severe degradation due to overgrazing and climate change. Protecting vegetation by fencing during the growing season is a widely applied management regime for restoration of degraded grasslands in this region. Here we investigated the effect of this restoration strategy on plant-pollinator communities and plant reproduction in the eastern Tibetan Plateau. We collected interaction and seed set data monthly across three grazed (grazed all year) and three ungrazed (fenced during growing season) alpine meadows in growing seasons of two consecutive years. Ungrazed meadows produced more flowers and attracted more pollinator visits. Pollination networks of ungrazed meadows were more modular and asymmetric. Furthermore, plants in ungrazed meadows were more robust to secondary species extinction than those in grazed meadows. The observed changes in the networks corresponded with higher seed set of plants that rely on pollinators for reproduction. Our results indicate that protection from grazing in growing seasons improves pollination network stability and function, and thus is a viable restoration approach for degraded meadows.